Regression Analysis on Crime Rates in Kaduna State from 2002-2016 - Rilwanu Yakubu Mohammed (Applied Mathematics and Computational Intelligence (AMCI), 2021)
The study determines the effect of unemployment on robbery, murder, rape, stealing, and drug abuse. Secondary method of data collection was used to collect the data from the Nigeria Police State Command, Kaduna and other law enforcement agencies in the state. Descriptive statistics and regression analysis were used to analyze the data obtained. The result showed that in 2003 reported cases were high in robbery with 132 persons, murder 69 persons, rape 32 persons, stealing 250 persons and drug abuse was 176 persons. While the year 2016 recorded low cases with robbery having 58 persons, murder 96 persons, rape 84 persons, stealing 94 persons and drug abuse 143 persons. Therefore, we concluded that there is no significant difference between unemployment rate and robbery, murder, stealing and drug abuse and the case of rape has p value 0.0104 < 0.05 which was statistically significant at 5% level of significant. The Nigerian police and other law enforcement agencies are therefore advised to improve on security measures in the state.